Tumor‐infiltrating lymphocyte quantification stratifies early‐stage human papillomavirus oropharynx cancer prognosis. (9th May 2019) - Faraji, Farhoud; Fung, Nicholas; Zaidi, Munfarid; Gourin, Christine C.; Eisele, David W.; Rooper, Lisa M.; Fakhry, Carole
Abstract : Objectives/Hypothesis: To evaluate if a simple method for assessing tumor‐infiltrating lymphocytes (TIL) in primary tumor specimens improves the prognostic value of the American Joint Committee on Cancer, 8th Edition (AJCC8) cancer staging system in human papillomavirus–positive oropharyngeal squamous cell carcinoma (HPV‐OPC). Study Design: Retrospective study. Methods: In this study, TIL density was quantified on hematoxylin and eosin (H&E)–stained specimens from patients presenting to Johns Hopkins Hospital between 2009 and 2017 who underwent primary surgical therapy and had primary tumor specimens available for analysis. The prognostic effect of TIL density was evaluated by Kaplan‐Meier method and Cox proportional hazards models considering recurrence‐free survival (RFS) as the primary outcome. Results: This study included 132 patients. Ninety‐five percent were classified by clinical criteria with AJCC8 early‐stage disease (stage I: 82%, stage II: 13%). After 84 months of follow‐up, 15 recurrences were observed. Among clinically early‐stage disease, TILhigh status was associated with improved RFS compared to TILlow ( P = .002). Adjusted analysis showed TILhigh status was associated with 79% lower risk of recurrence than TILlow (adjusted hazard ratio [aHR]: 0.210, 95% confidence interval [CI]: 0.061‐0.723). In clinical stage I disease, TILhigh status was associated with improved RFS compared to TILlow in both univariate and multivariate analyses (hazard ratio: 0.235, P = .021; aHR: 0.218; 95% CI: 0.058‐0.822). TIL density similarly stratified risk in pathologically staged disease. Conclusions: In patients with AJCC8 stage I disease, low TIL density was associated with diminished RFS. Our data suggest that assessing TIL density on H&E‐stained primary tumor specimens may enhance the prognostic resolution of the AJCC8 staging criteria for HPV‐OPC. Level of Evidence: 4 Laryngoscope, 130:930–938, 2020